Investigation of the accuracy of determining planned and altitude coordinates based on survey data by unmanned aerial vehicles - Yanchuk, Oleksandr; Trokhymets, Serhii; Yanchuk, Ruslan; Bukhalska, Tetiana (Geodesy and Cartography, 2023)
Experimental studies of the accuracy of determining the plan and altitude coordinates were obtained from aerial photography materials and measured by a satellite receiver in real time. The study was conducted for aerial photography materials obtained from heights of 100 and 200 meters. In addition, the accuracy researched of using a different number of ground control points for georeferencing images – 18 and 5. Accuracy assessment was performed separately for the plain area and the area with rugged terrain.